PENGEMBANGAN LKM GAPOKTAN DI KABUPATEN GUNUNG KIDUL DAERAH ISTIMEWA YOGYAKARTA - Nalinda, Rika (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2015)
Research of development microfinance institutions (MFIs) Gapoktan in in the district of Gunung Kidul conducted from March to December 2014, aims to determine the factors that affect the sustainability of MFIs Gapoktan. The data used are primary data obtained from the Extension Workers, and MFIs Gapoktan. Secondary data from the Department of Agriculture, BP2KP and BPP. Sample MFIs Gapoktan. determined by purposive with a variety of conditions is less developed, undeveloped and developed worlds. Data were collected by interview and discussion. Analysis of data using multiple linear regression analysis. Factors that affect the sustainability of MFIs Gapoktan in Gunung Kidul consists of legality aspects, aspects of capability management, aspects of capital support, feasibility aspects, aspects of the characteristics of the MFI, and aspects of the real guidance of the business. Results of the analysis showed that all six of these factors effect no significant effect on the development of MFIs Gapoktan in Gunung Kidul.